Transformasi tiktok dari media hiburan menjadi sarana ekonomi dan edukasi di kalangan pelajar kota Malang - Fahreza, Ahmad Rosyid; Machbubi, Audrey Syafa (Maliki Interdisciplinary Journal, 2026)
The transformation of social media from a single function to a multifunctional one is a significant phenomenon in the digital era. This study examines the shift in TikTok's role from an entertainment medium to an economic and educational tool among students in Malang City. The research aims to analyze the evolution of this transformation, interpret it through the lens of Herbert Spencer's evolution theory, and understand it from an Islamic sociology perspective. The method used is descriptive qualitative with a library research approach, processing data from relevant journals, books, and scientific articles. The results show a significant functional differentiation of TikTok; students are not only passive consumers but also economic agents (through affiliate features and TikTok Shop) and educational agents (through micro-learning content). Herbert Spencer's perspective explains this phenomenon as social evolution characterized by functional integration and differentiation, as well as the law of survival of the fittest. Meanwhile, the Islamic sociology perspective, particularly the thought of Ibn Khaldun and QS. Ar-Ra'd: 11, confirms that this change is a form of conscious human adaptation as agents of change to achieve benefit (maslahah). In conclusion, TikTok has evolved into a complex digital ecosystem, reflecting the progress of digital civilization that aligns with the principles of social change in Islam.